Adolescent autonomy: Role of father’s involvement and family functioning - Arcivid Chorynia Ruby; Prapti Madyo Ratri; Fajar Kawuryan; Kholifah Umi Sholihah; Adnan Fadkhurosi; Tinon Citraning Harisuci (University of Merdeka Malang, 2025)
Adolescence is a transitional period marked by increasing self‑direction. This study examined whether father involvement and family functioning are associated with adolescent autonomy. Using multistage cluster sampling across several districts/cities in Central Java, Indonesia, we analysed survey data from 929 adolescents aged 12–19 years. Participants completed validated scales of adolescent autonomy, family functioning, and father involvement. Statistical analysis was conducted using the bootstrapping technique to test the strength of the relationship and its effects. The results indicated that both family functioning and father involvement had a significant positive relationship with adolescent autonomy. Increased family functioning and active father involvement were associated with higher levels of autonomy in adolescents. Findings suggest that adolescents tend to report higher autonomy in supportive family climates with engaged fathers, informing family‑based strategies to strengthen self‑regulation and decision‑making. These insights provide practical implications for strengthening adolescent psychosocial development through family-based interventions.